Asymmetric Magnesium‐Catalyzed Hydroboration by Metal‐Ligand Cooperative Catalysis. Issue 49 (23rd October 2019) - Falconnet, Alban; Magre, Marc; Maity, Bholanath; Cavallo, Luigi; Rueping, Magnus
Abstract: Asymmetric catalysis with readily available, cheap, and non‐toxic alkaline earth metal catalysts represents a sustainable alternative to conventional synthesis methodologies. In this context, we describe the development of a first Mg II ‐catalyzed enantioselective hydroboration providing the products with excellent yields and enantioselectivities. NMR spectroscopy studies and DFT calculations provide insights into the reaction mechanism and the origin of the enantioselectivity which can be explained by a metal‐ligand cooperative catalysis pathway involving a non‐innocent ligand. Abstract : Mg‐ligand cooperative activation of HBpin : The enantioselective magnesium‐catalyzed hydroboration of ketones using a ( R )‐(+)‐BINOL derivative as a chiral ligand affords excellent yields and enantioselectivities. Experimental investigations together with DFT calculations provide insight into the reaction mechanism and the origin of enantioselectivity.